(untitled) (Eurasian Journal of Philology Science and Education, 2016)
In the article deep connections of work of О. of Сулейменова are examined with the past. What larger writer, the wider hypertext space of his work, i.e. connection with different epochs, facts, personalities. Concept hypertext space close by value to the continuum. The concept of hypertext space is considered on the example of О. Suleymenov’s work.